HUBUNGAN PENGETAHUAN DENGAN HASIL BELAJAR PRAKTEK PEMANGKASAN RAMBUT SISWA JURUSAN TATA KECANTIKAN RAMBUT SMK NEGERI 3 PAYAKUMBUH - Yolalalita, Suci; Hayatunnufus, Hayatunnufus; Yanita, Merita (Journal of Home Economics and Tourism, 2016)
This research is written to describe the correlation between students’ knowledge and the learning outcomes of practical subjects about hairdressing of students of hair beauty department of SMK 3 Payakumbuh. This research is a quantitaive-descriptive research within 40 students who have learned Basic Haircut. The sampling technique used in this research is total sampling. The technique of data collection which is used is using objective test in which the validity and the realibility  has been tested. The analysis of the level of respondents achievement using the students learning outcomes of percentage formula and the average score, test requierement analysis by normality test and linerity test, correlation coefficient analysis with Product Moment correlation and T-test to analyze the correlation coefficient significance and hypothesis test. The result of this research shows that ; (1) The percentage of the knowledge of hairdressiing is 59%  which is included in low category (2) the learning outcomes of hairdressing subject has average score rate 74, this score is still below of KKN, that is >_ 80, (3) there is a positive-significant correlation between the knowledge and the learning outcomes of hairdressing  subject with evidentiary value of T- test > t table (27,247>2,201) which means that Ha is acceptable.   Keywords: Knowledge, Learning Outcomes